Provide a model of the impact of Value Engineering and Organizational Agility in improving the competitiveness of construction industry companies - Mohammad Jahankohan; Sayed Alireza Mirmohammadsadeghi (مهندسی و مدیریت ساخت)
The increasing speed of changes in technologies and markets and in customers nature and on the other hand the intensifying competition between organizations, has led companies to intensively seek new competitive advantages to excel among competitors and do better in meeting the needs and demands of customers. Hence, it is crucial to have a new solution which is to move towards the creation of organizations that can be fast and flexible in responding to changes in unstable and unpredictable environments. therefore It is imperative for companies to either directly or indirectly,deal with the changes that can threaten their ability to survive Agile management and value engineering are creating new paradigms for managing highly competitive organizations and firms . In this article, authors are seeking to improve the competitiveness of Iranian contractor companies by utilizing value engineering and agile approaches, first, by performing library studies, competitiveness indicators and factors that have effects on them were identified and have been presented. with the results from conducting interviews with Experts ,we screened these indicators and found their effective factors and then with the help of a questionnaire these indicators were ranked. Then, the components affecting the organization's agility were identified and finally,by conducting value engineering in projects, improvements that affect the competitive advantages of companies were identified and a conceptual model of the combination of the three themes was presented. In this model, we reached the answers to the research's questions.(hypothesis)